La gestione degli Incendi boschivi mediante l’utilizzo di moderne tecniche cartografiche. L’esperienza del Corpo Nazionale dei Vigili del Fuoco. - Cuzzocrea, Fabio; Priori, Fabrizio (GEOmedia, 2015)
The management and planning of the fleet of Canadair for the prevention and coordination of emergencies in times of maximum criticality is the key to save our territory. The areas most subject to forest fires are constantly monitored by the air fleet that is managed in real time with programs for geolocation of the aircraft.